2006
DOI: 10.1124/mol.106.026450
|View full text |Cite
|
Sign up to set email alerts
|

Modification of OATP2B1-Mediated Transport by Steroid Hormones

Abstract: The family of the organic anion transporting polypeptides forms an increasing group of uptake transport proteins with a wide substrate spectrum. Although the expression of some members of this group, such as organic anion transporting polypeptide (OATP)-A or C, is limited to special tissues (such as liver or brain), the organic anion transporting polypeptide 2B1 (OATP-B/SLCO2B1) is expressed in many organs, including liver, placenta, mammary gland, brain, and intestine. However, little is known about its funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
75
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 36 publications
13
75
0
Order By: Relevance
“…Uptake was saturable with apparent K m and V max values of 13.8 ± 2.5 lM and 518 ± 30 pmol/mg/min, respectively. The K m value is comparable with the values published in the literature (Grube et al, 2006a;Nozawa et al, 2004;Tamai et al, 2001). …”
Section: Characterization Of Oatp2b1-expressing Cellssupporting
confidence: 81%
“…Uptake was saturable with apparent K m and V max values of 13.8 ± 2.5 lM and 518 ± 30 pmol/mg/min, respectively. The K m value is comparable with the values published in the literature (Grube et al, 2006a;Nozawa et al, 2004;Tamai et al, 2001). …”
Section: Characterization Of Oatp2b1-expressing Cellssupporting
confidence: 81%
“…On the other hand, indomethacin, ketoprofen, and naproxen stimulated OATP2A1-mediated PGE 2 uptake in a concentration-dependent manner. Although the molecular mechanism underlying the stimulatory effect of these compounds on the OATP2A1 function is unknown, similar findings showing the stimulation of uptake transporter activities by drugs and endogenous substrates have been reported previously for transporters other than OATP2A1 (Grube et al, 2006;Bachmakov et al, 2008). Regarding OATP2A1, Lu et al (1996) also observed a slight increase of 14% in OATP2A1-mediated PGE 2 transport at a concentration of 10 M indomethacin, whereas at 100 M indomethacin the PGE 2 uptake was decreased to 82.5% of control.…”
Section: Downloaded Fromsupporting
confidence: 61%
“…Coadministration of gemfibrozil was predicted to have a minor impact on atorvastatin uptake CL, whereas coadministration of atazanavir, cyclosporine, lopinavir, and rifampicin was predicted to give a more pronounced reduction in atorvastatin uptake. previously in in vitro studies (Grube et al, 2006). To our knowledge, though, it has never been observed in vivo.…”
Section: Discussionmentioning
confidence: 81%